PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS PENDEKATAN DEEP LEARNING PADA MATA PELAJARAN IPA KELAS VII SMP - Juliani, Mustika; Rosmaria; Pratiwi, Rahmi; Elsa Masriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop interactive multimedia based on the deep learning approach for science subjects (IPA) in class VII of Junior High School (SMP). The development model used is the 4-D model (Define, Design, Develop, Disseminate) by Thiagarajan et al. (1974). The research was conducted at SMP Pertiwi 2 Padang. Data collection instruments included validation assessment sheets for media experts and material experts, as well as practicality questionnaires for students. The validity of the interactive multimedia was assessed by two media validators and one material validator using a 5-point Likert scale. The results showed that the material validation reached an average score of 4.81 (Very Valid), media validation 1 reached 4.95 (Very Valid), and media validation 2 reached 4.80 (Very Valid). The practicality test involving 20 students of class VII obtained an average score of 4.92 (Very Practical). These findings indicate that the interactive multimedia based on the deep learning approach for IPA in class VII SMP is valid and practical as a learning medium. The media integrates meaningful learning, mindful learning, and joyful learning elements to create engaging, meaningful, and contextual science learning experiences